Optimalisasi Produk Lokal sebagai Daya Tarik Kampung Wisata Pakintelan Semarang - Aurilia Triani Aryaningtyas; Suwarti Suwarti; Gana Wuntu; Tiara Sanika Langsa Putriningsih; Amelia Lufitta Putri (Jurnal Kajian Ilmiah, 2025)
This study examines the optimization of local products as the main attraction of Pakintelan Tourism Village in Semarang. The primary issues identified include inadequate promotion and infrastructure to support the potential of local products such as durian and bamboo  crafts. Through a qualitative approach and descriptive method, this research explores community involvement, collaboration with government and businesses, and challenges in utilizing local products. The findings indicate that local products have significant potential to enhance tourism appeal and local economy. However, limitations in infrastructure and promotion  remain major obstacles. Strategic recommedations include enhancing digital promotion, developing infrastructure, and fostering multi-stakeholder collaboration. The study also highlights the need for further research to evaluate the long-term impact of local product development initiatives on community welfare.